2022
DOI: 10.1172/jci.insight.161438
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-derived cytokine TSLP promotes growth and metastasis of melanoma by regulating the tumor-associated immune microenvironment

Abstract: Malignant melanoma is a major public health issue displaying frequent resistance to targeted therapy and immunotherapy. A major challenge is to better understand how melanoma cells evade immune elimination and how tumor growth and metastasis is facilitated by tumor microenvironment. Here, we show that expression of the cytokine TSLP by epidermal keratinocytes is induced by cutaneous melanoma in both mice and humans. Using genetically engineered models of melanoma and tumor cell grafting combined with TSLP knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Although substantial research has been done on the function of TSLP in Th2 immune responses, more recent investigations have discovered that TSLP also has a growing role in allergic reactions and cancer. [29,30] The development of hematological tumors as well as solid tumors like breast, colon, and pancreatic cancers have been linked to TSLP, while TSLP signaling provides protection against skin cancers [29][30][31][32]. On the other hand, Yao et al reported that TSLP promotes the metastasis and growth of melanoma by stimulating CD4 T cells and dendritic cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial research has been done on the function of TSLP in Th2 immune responses, more recent investigations have discovered that TSLP also has a growing role in allergic reactions and cancer. [29,30] The development of hematological tumors as well as solid tumors like breast, colon, and pancreatic cancers have been linked to TSLP, while TSLP signaling provides protection against skin cancers [29][30][31][32]. On the other hand, Yao et al reported that TSLP promotes the metastasis and growth of melanoma by stimulating CD4 T cells and dendritic cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…They may release chemical signals that attract immunosuppressive cells such as regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs). These suppressive immune cells create an immunosuppressive shield around the tumor, preventing the effective activation and functioning of antitumor immune cells [78][79][80] .…”
Section: Tumor Microenvironment Changesmentioning
confidence: 99%
“…Melanoma induces keratinocytes to generate cytokine thymic stromal lymphopoietin (TSLP), transmits signals through the TSLP receptor of DC, promotes the expression of GATA3+Treg, and inhibits the activity of IFN-γ and the proliferation of CD8+ T cells. In lung squamous cell carcinoma (LUSC), it has also been found that the tumor produces immunosuppression through high expression of anti-inflammatory factors, such as TGFβ and CCL18 [ 81 - 84 ] . Studies have found that Treg can cooperate with cancer cells to suppress immune activity.…”
Section: Mechanism Of Resistance To Immunotherapymentioning
confidence: 99%
“…[98][99][100] In the context of malignant melanoma, a study by Yao et al T cell proliferation and IFNγ production, thus suggesting that TSLP plays a crucial role in shaping a pro-tumoral immune microenvironment in malignant melanoma. 101…”
Section: Thymic Stromal Lymphopoietin (Tslp)mentioning
confidence: 99%
“…Pro-tumoral Promotes proliferation, migration and invasion of melanoma cells and VM tube formation through ST2 41 Activation of macrophages which protect melanoma cells from killing mediated by TILs by upregulating the expression of MMP-9 87,88 Anti-tumoral Activation of CD8 + T cell-dependent mechanism [90][91][92][93][94] Yao et al 101 TSLP Pro-tumoral Promoting melanoma progression and metastasis 101 Benatar et al…”
Section: Il-33mentioning
confidence: 99%